3-D retina organoids: Building platforms for therapies of the future. (5th June 2018) - Mazerik, Jessica N; Becker, Steven; Sieving, Paul A
Across scientific disciplines, 3-D organoid culture systems offer platforms to integrate basic research findings with clinical care. The National Eye Institute mounted a 1.1 million 3-D Retina Organoid Challenge. Organoids developed through the Challenge will be valuable resources for drug screening, disease modeling, and precision and regenerative medicine.